Monitoreo del ruido ambiental en los aserraderos del perímetro urbano en el cantón Salcedo, provincia de cototopaxi, período 2014 - 2015 - Sánchez Vargas, Jorge Enrique (2015)
One of the most common environmental problems that disproportionately strong effect the human being is the undesirable noise levels increase. The noise exposure prolonged, whether in daily life or in the workplace can cause medical problems such as: hypertension and heart disease. This research was based on the noise study which is generated in sawmills which are located within the urban area in Salcedo Canton. Also, it helps to identify the processes and machinery that has in their industries. This study applied a sonómetro type 2….